Conductivity Dispersion Characteristic of Oilwell Cement Slurry during Early Hydration - Ridha, Syahrir (2010)
The influence of water to cement ratio and degree of hydration to the dispersion characteristic of oilwell cement slurries during 24 hrs of hydration is evaluated and expressed in the form of magnitude and frequency effect at above cutoff frequency. It is observed that the magnitude of conductivity dispersion increases with the reduction in water content and pore volume. At initial hydration, the dispersion characteristic appears in the minimum value and raises as hydration continue. The frequency effect is growth as the hydration and saline concentration increases. It is shown that the single frequency measurement for evaluating the cement slurries properties may not be reliable. An implicit correlation to the interface conductivity is indicated from dispersion respond throughout hydration process.